Help or hindrance : the image of "self as teacher" held by New Zealand first year teachers : a thesis presented in partial fulfilment of the requirements for the degree of Master of Education at Massey University, Palmerston North, New Zealand - Smales, Jeanette (Massey University, 2002)
This study pioneers research into the 'self as teacher' image of New Zealand first year teachers. A personal narrative approach allowed the researcher to explore: how New Zealand first year teachers metaphorically perceive 'self as teacher' image; the events, situations, and issues that these teachers feel enhance, challenge, or undermine initial 'self as teacher' image; and the role 'self as teacher' image plays in the professional development of New Zealand first year teachers. The implications of the above for preservice and inservice providers of teacher education are discussed. The study demonstrates that 'self as teacher' image is not constant, it is shifting and complex. The research indicates that the metaphors first year teachers use to define 'self as teacher' images are indicative of their professional development stage. Although first year teachers must come to terms with a complex array of factors as they interact within the wider school context, if they have been adequately prepared and are sufficiently supported during the first year of teaching, they will professionally grow and meet the challenges. If first year teachers are supported they can develop a patchwork of metaphors defining 'self as teacher' image that appropriately informs their practice so they can accommodate to the particular context in which they need to operate. The research indicates that preservice and inservice teacher educators need to assist beginning teachers to identify and examine 'self as teacher' image and take ownership of their professional development so they can be the author of the teacher they are becoming.
Keywords: New Zealand First Year Teachers; Attitudes